2022
DOI: 10.1142/s0218348x22500797
|View full text |Cite
|
Sign up to set email alerts
|

Information Dimension of Galton Board

Abstract: In this paper, we relax the definition of Rényi information dimension. The power law of the Entropy-Layer in the Galton board is discovered and we calculate its information fractal dimension. When the Galton board is extended to bias or three-dimensional space, we get the same fractal features. In addition, according to the connection between Pascal’s triangle and the Poisson distribution, we find constrained Poisson distribution groups with the same information dimension. This is the first time the informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The theory of belief function is an uncertain reasoning one initiated by Dempster [29] and inherited and developed by Shafer [30], therefore also known as Dempster-Shafer theory (DST). After half a century of development, the theory has been well developed and played an important role in a wide variety of fields, such as decision-making [40][41][42] and information fusion [43][44][45]. Suppose that the answer to the question of concern consists of a finite set of mutually exclusive elements, called frame of discernement (FoD), expressed as = {θ 1 , θ 2 , .…”
Section: Belief Function Theorymentioning
confidence: 99%
“…The theory of belief function is an uncertain reasoning one initiated by Dempster [29] and inherited and developed by Shafer [30], therefore also known as Dempster-Shafer theory (DST). After half a century of development, the theory has been well developed and played an important role in a wide variety of fields, such as decision-making [40][41][42] and information fusion [43][44][45]. Suppose that the answer to the question of concern consists of a finite set of mutually exclusive elements, called frame of discernement (FoD), expressed as = {θ 1 , θ 2 , .…”
Section: Belief Function Theorymentioning
confidence: 99%
“…Recent research has indicated that D-S evidence theory can adhere to fractal laws [10] . Fractal entropy, proposed by Zhu and Deng, serves as a model for the transformation of signal probability [11] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many attentions were paid to the fractal feature of evidence theory Zhou et al. ( 2022b ); Zhu et al. ( 2020 ).…”
Section: Introductionmentioning
confidence: 99%